Comparing the effectiveness of Henderson instructions and expert testimony: Which safeguard improves jurors’ evaluations of eyewitness evidence? - Jones, Angela M. (Journal of experimental criminology, 2017)
The New Jersey Supreme Court recently determined that jurors may not be able to effectively evaluate eyewitness evidence on their own. As a result, the Court proposed the use of judicial instructions to assist jurors (called Henderson instructions) and suggested the implementation of these instructions would reduce the need for expert testimony. We tested the efficacy of these instructions compared to alternative instructions and expert testimony.